(untitled) (Research, Society and Development, 2021)
This paper aims to understand and document the main results obtained from studies of intermittent turbulent events of variable intensity and periodicity, which provide episodic connection between the canopy and the atmosphere and can cause oscillatory procedures in the nocturnal boundary layer (CLN) performed exclusively on the Amazon Tall Tower Observatory (ATTO) experimental site through a narrative literature review of the main articles published during the period 2012 to 2021. A literature search was carried out in the ATTO project database, accessed on September 24, 2021 , where this database has all peer-reviewed publications in journals made in the ATTO project between 2012 and 2021. All articles were reviewed and highlighted here so that the main results were described, then from 81 publications in this total. database only 3 articles are categorized as studies on turbulent events as intermittent in the CLN. It is concluded that inside the canopy, CO2 fluxes and latent heat are dependent on processes with long time scales. Since this low frequency shift tends to be increased under very stable conditions, the total scalar flow within the canopy may be greater on very stable nights than on weakly stable nights. On very stable nights, turbulent fluxes are effectively suppressed at 80 m, pointing out that the thickness of the shallow boundary layer can be found in these situations.